Estimation of thiocetam influence on glutathione link of thiol disulfide cerebral system in conditions of experimental chronic ischemia - A. V. Demchenko; І. F. Belenichev (Patologìâ)
Aim. Pharmacological remodeling of pathologic changes when cerebral ischemia takes place is actual task for today. With the purpose of thiocetam neuroprotective properties studying in conditions of experimental chronic cerebral ischemia the investigations of 45 white rats with simulated chronic cerebral ischemia have been carried out.